Promoting Students' Science Process Skills Through Predict Discuss Explain Observe Discuss Explain Implementation - Risa Dwita Hardianti; Indhah Ulya Permatasari (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
The ideal science classroom prepares students to enhance not only mastery knowledge but also skills. Certain skills can be developed during the process of learning science. One of the skills that expected to be possessed is Science Process Skills (SPS). SPS can be gain by applying Predict-Discuss-Explain-Observe-Discuss-Explain (PDEODE). Therefore, the intent of this study was analyzing students’ science process skills after the implementation of PDEODE. Measurements of SPS were obtained by collecting data from three domains of learning. SPS of students ranges from good to excellent level. About 18,29% students got excellent marks of SPS while most of them (81,71%) successfully reached good level. To put in a nutshell, PDEODE learning assisted students to attain all indicators of SPS.